SIFAT-SIFAT PEMETAAN BILINEAR - Ruhama, Mustafa A. H. (Universitas Khairun, 2012)
Let U, V, and W are vector spaces at the same field, phi: U X V ? W bilinear mapping, if W = C that phi is bilinear functional. The collection of all bilinear mapping phi: U X V denoted with B(U, V, W). Problems we will discuss about some properties at bilinear mapping. Furthermore will see B(U, V, W) is vector space toward operation ( phi + psi) (x,y) = phi(x,y) + psi(x,y) and (lamdaphi)(x,y) =lamdaphi(x,y) for all scalar lamda, x elemen U, y elemen V and phi, psi elemen B(U, V, W).